1976
DOI: 10.1159/000175689
|View full text |Cite
|
Sign up to set email alerts
|

Development of Digestive and Absorptive Function in the Human Fetus

Abstract: In the mature human newborn infant, only pancreatic α-amylase shows a very low but highly inducible activity. Other digestive enzymes, although not yet at adult levels, increase rapidly with age. Intestinal absorptive functions develop already during early and mid-pregnancy and are mostly at adult levels in the newborn infant. Fat absorption is usually low in the premature infant and increases rapidly during the first month.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1979
1979
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…It is reported that bile is secreted from 12 weeks of gestation in the fetus. 15,16 Concentrations of bilirubin and bile acid in the amniotic fluid were reported to be high in cases of intestinal obstruction distal to Vater ampulla. [17][18][19] These findings suggest that UCU is closely related to in utero regurgitation of bile.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that bile is secreted from 12 weeks of gestation in the fetus. 15,16 Concentrations of bilirubin and bile acid in the amniotic fluid were reported to be high in cases of intestinal obstruction distal to Vater ampulla. [17][18][19] These findings suggest that UCU is closely related to in utero regurgitation of bile.…”
Section: Discussionmentioning
confidence: 99%
“…Similar in vitro studies lead to the prediction that the human fetus is able to absorb glucose and digest all three disaccharides (18). I n vitro studies, however, cannot predict whether the human fetus will also develop an increase in IH+I and lactate with carbohydrate feeding.…”
Section: Speculationmentioning
confidence: 97%
“…still lack sucrase and only have very low levels of maltase (21). It is in contrast to the situation in the human fetal intestine where high levels of sucrase and maltase are present by the third trimester (18). Because the pH optimum for maltase is close to 6 (12).…”
Section: Pooled Datamentioning
confidence: 99%
“…In infants, secretion outputs and enzyme activity levels mature at very different rates: gastric lipase activity already reaches adult levels by 3 months (Ménard et al, 1995), whereas pancreatic -amylase only does so after 3 years of age (Zoppi et al, 1972). In contrast, the small intestine of human infants is mature at birth and can handle the various nutrients (Shmerling, 1976). Despite the slow maturation of pancreatic amylase, most cooked starches are digested and absorbed almost completely (De Vizia et al, 1975).…”
Section: Digestion and Absorptionmentioning
confidence: 99%